1983
DOI: 10.1111/j.1365-2125.1983.tb02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Active metabolites of acenocoumarol: do they contribute to the therapeutic effect?

Abstract: 1 The pharmacokinetics and pharmacodynamics of racemic acenocoumarol (AC), the amino (AM) and acetamido (AA) derivative were investigated in healthy volunteers after administration of a single oral (10 mg) dose. 2 All three coumarins were rapidly absorbed from the gastrointestinal tract. The elimination half-lives were 10.9, 10.4, and 4.1 h, for AC, AM and AA, respectively. 3 After the oral administration of AC, no AM and AA was detected in the plasma, and less than 1% of the dose was recovered in the urine (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Whereas their mechanism of action is similar, i. e. they suppress the vitamin K dependent carboxylation of glutamic acid residues in coagulating factor precursor proteins (2), their pharmacokinetics differ highly. The biological half-life of phenprocoumon (3-5 days) (3,4) is much longer than that of warfarin (t,,, _ 30-80 h) (4), that of acenocoumarol is much shorter (ty, about 10 h) (5). These characteristics are reflected in the time needed for the blood clotting activity (for instance prothrombin time) to recover after cessation of drug administration: about 2 days for acenocoumarol, 3-5 days for warfarin, and 8-15 days for phenprocoumon (6).…”
mentioning
confidence: 99%
“…Whereas their mechanism of action is similar, i. e. they suppress the vitamin K dependent carboxylation of glutamic acid residues in coagulating factor precursor proteins (2), their pharmacokinetics differ highly. The biological half-life of phenprocoumon (3-5 days) (3,4) is much longer than that of warfarin (t,,, _ 30-80 h) (4), that of acenocoumarol is much shorter (ty, about 10 h) (5). These characteristics are reflected in the time needed for the blood clotting activity (for instance prothrombin time) to recover after cessation of drug administration: about 2 days for acenocoumarol, 3-5 days for warfarin, and 8-15 days for phenprocoumon (6).…”
mentioning
confidence: 99%
“…[1][2][3]. It is important to determine the individual variations in pharmacokinetics in healthy volunteers (16).…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned model was considered adequate for the examination of systemic availability and the first-pass elimination of acenocoumarol, because the drug corresponds to the assumptions of the model (2)(3)(4). It was therefore of practical importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the AUC 0-48 and AUC 0-∞ values of acenocoumarol for 1, 4, 10 and 12 mg dose (Table 1(Tab. 1); References in Table 1: Huang et al, 2008[2]; Masche et al, 1999[3]; Popovic et al, 1994[4]; Rolan et al, 2003[6]; Sasso et al, 2012[8]; Sunkara et al, 2004[9]; Thijssen and Baars, 1983[10]; Thijssen and Hamulyàk, 1989[12]). No other information on AUC 0-48 and AUC 0-∞ were available with the 2, 8 and 16 mg dose.…”
Section: mentioning
confidence: 99%